Mobile ECG monitoring for atrial fibrillation management: A literature review - Vincent Pearson (International Journal of Advanced Health Science and Technology, 2022)
Atrial fibrillation is the most prevalent arrhythmia associated with the risk of developing stroke and heart failure. Catheter ablation and electrical cardioversion are standard interventional procedures to treat atrial fibrillation. Patients are recommended to undertake regular heart rhythm assessment after the procedure due to the high recurrence rate of atrial fibrillation. Multiple mobile applications with high sensitivity and accuracy rates in rhythm analysis have been developed to support on-demand rhythm monitoring. This literature review aims to provide an overview of emerging evidence about the impact of mobile ECG monitoring on AF management. Keywords and index terms used in the search strategy include "atrial fibrillation" AND "mhealth" OR "mobile health" OR "mobile app" OR "mobile application" OR smartphone OR mobile AND "electrocardiography", "electrocardiogram" OR "ECG" OR "monitoring". A search using all identified keywords and index terms was undertaken across the following databases: PubMed, CINAHL, and EMBASE. Incorporating the novel mobile ECG monitoring technology in the guideline-adherent integrated AF care model may reduce rehospitalisation, improve HRQoL, and better patient clinical outcomes. Mobile applications with ECG monitoring functions can provide user-friendly on-demand rhythm monitoring, facilitating the early detection of recurrent AF post-ablation.